Pengaruh Pengetahuan Akuntansi Syariah dan Gender terhadap Sikap Mahasiswa Akuntansi pada Konteks Bunga atau Riba - Widia Wati; Salma Taqwa (Universitas Negeri Padang, 2026)
This study aims to analyze the effect of knowledge of sharia accounting and gender on the attitude of accounting students in the context of interest or usury. This research uses a quantitative approach. The sampling method in this study used purposive sampling technique. The sample consists of accounting students in Padang City who have taken Islamic accounting courses. The Krejcie and Morgan table was used to determine the sample size, which was 248 students. The results of this study indicate that: 1) Sharia accounting knowledge does not have a significant effect on the attitude of accounting students in the context of interest or usury, although it shows a positive relationship direction. Therefore, the hypothesis is rejected; 2) Gender does not significantly influence accounting students' attitudes toward interest or usury. Therefore, the hypothesis is rejected. These findings imply that Islamic accounting education should not only emphasize conceptual knowledge but also strengthen behavioral and ethical dimensions to enhance students’ understanding and ethical consistency toward the prohibition of usury.